Financial factors as antecedents of economic well-being and mediation effect of technology adoption - Wijekoon, Rusitha; Sabri, Mohamad Fazli; Ahmad, Nobaya; Abdul Rahim @ Abdul Wahab, Husniyah; Ahmad Suhaimi, Siti Shazwani (Malaysian Consumer and Family Economics Association, 2021)
Due to the limited number of previous studies and their existing inconsistencies on the identification of related financial antecedents of individual economic well-being, this study examined the effect of the financial antecedents, such as financial knowledge, financial behavior, and money attitudes on both technology adoption and economic well-being in order to address the existing gaps in the literature. Moreover, according to the authors' best knowledge, the mediating role of agricultural technology adoption was investigated the first time between financial antecedents and economic well-being. A survey of 416 Sri Lankan coconut growers was undertaken using a multi-stage random sampling procedure. All direct associations between financial knowledge, financial behavior, money attitudes, and economic wellbeing were significant with the PLS-SEM analyses. They all explained 91.1% of the overall variance in economic well-being. Moreover, the mediating role of agricultural technology adoption was also found significant for all relationships between financial antecedents and economic well-being. The mediating model was also clarified 2.2% of the additional variance in economic well-being. Further, three financial antecedents were also detected as positive antecedents of agricultural technology adoption and explained 80% of the variance in technology adoption. Hence, the present study results are important to broaden the understanding of the effect of financial antecedents on agricultural technology adoption and economic well-being to address the existing gaps in the literature. Furthermore, it guides policymakers in future policy implications to facilitate well-being by properly comprehending financial-related antecedents among individuals, especially in developing countries, to reduce their poverty through agricultural technology adoption.